Molecular and cytogenetic characterization of wild Musa species - Cizkova, J.; Hribova, E.; Christelova, P.; Houwe, Ines van den; Hakkinnen, M.; Roux, N.; Swennen, Rony L.; Doležel, Jaroslav (Public Library of Science, 2015)
The production of bananas is threatened by rapid spreading of various diseases and adverse environmental conditions. The preservation and characterization of banana diversity is essential for the purposes of crop improvement. The world's largest banana germplasm collection maintained at the Bioversity International Transit Centre (ITC) in Belgium is continuously expanded by new accessions of edible cultivars and wild species. Detailed morphological and molecular characterization of the accessions is necessary for efficient management of the collection and utilization of banana diversity. In this work, nuclear DNA content and genomic distribution of 45S and 5S rDNA were examined in 21 diploid accessions recently added to ITC collection, representing both sections of the genus *Musa*. 2C DNA content in the section Musa ranged from 1.217 to 1.315 pg. Species belonging to section Callimusa had 2C DNA contents ranging from 1.390 to 1.772 pg. While the number of 45S rDNA loci was conserved in the section Musa, it was highly variable in Callimusa species. 5S rRNA gene clusters were found on two to eight chromosomes per diploid cell. The accessions were genotyped using a set of 19 microsatellite markers to establish their relationships with the remaining accessions held at ITC. Genetic diversity done by SSR genotyping platform was extended by phylogenetic analysis of ITS region. ITS sequence data supported the clustering obtained by SSR analysis for most of the accessions. High level of nucleotide diversity and presence of more than two types of ITS sequences in eight wild diploids pointed to their origin by hybridization of different genotypes. This study significantly expands the number of wild *Musa* species where nuclear genome size and genomic distribution of rDNA loci is known. SSR genotyping identified *Musa* species that are closely related to the previously characterized accessions and provided data to aid in their classification. Sequence analysis of ITS region provided further information about evolutionary relationships between individual accessions and suggested that some of analyzed accessions were interspecific hybrids and/or backcross progeny.